Korean Pharmacopuncture Meets Austrian High-Tech Acupuncture - A Short Review Article Including a Bibliometric Analysis of Pharmacopuncture over the Last 15 Years - Pharmacopuncture and Europe - Litscher Daniela; Litscher Gerhard; Kang Dae-In (Korean Pharmacopuncture Institute, 2013)
Objective: Pharmacopuncture, a new therapy in traditional medicine, has attracted significant attention since its introduction to the Western world. This short review article employs a database analysis to examine the profile of publication activity related to pharmacopuncture. Methods: Three databases were searched: PubMed, Embase, and Cochrane. About 300 papers related to the topic "pharmacopuncture" were found in these three most-commonly-used databases. Results: Fourteen papers are described in detail and are discussed in the context of the research performed at the Medical University of Graz, especially by the Frank Bahr Research Group "Auriculomedicine and Pharmacopuncture." Conclusion: High-tech research methods concerning future pharmacopuncture studies are briefly discussed.